Assessment of adequacy of tools and measures applied by enterprises for production process improvement. Issue 1 (1st January 2020) - Hamrol, Adam; Grabowska, Marta
ABSTRACT: The article presents a new approach to assess improvement actions performed in production enterprises. The evaluation criterion is adequacy of diagnostic tools that were used as improvement measures. Three aspects of improvements have been analysed: nature of problems that are the starting point for undertaking a project, types of tools used to identify problems, and types of measures introduced. Data obtained from completed projects is processed and verified statistically with use of the so-called maturity matrix. The presented methodology may be helpful in taking actions aimed at increasing effectiveness of improvement activities in an enterprise.